73 Maternal and Fetal Outcomes in Women with Aortopathy: Experience in a Tertiary Joint Cardiac Obstetric Centre. (3rd June 2016) - Plunkett, Emma; Bull, Suzanna; Gertig, Ruth; Bowater, Sarah; Clift, Paul; Hudsmith, Lucy; Thorne, Sara; Morris, Katie; Selman, Tara; Thompson, Peter
Abstract : Introduction: Pregnancy is associated with increased risk of cardiovascular complication for women with aortic pathology. The University Hospitals Birmingham (UHB) and Birmingham Women's Hospital (BWH) joint cardiac obstetric service sees women with aortopathy for pre-pregnancy assessment and counselling and subsequently manages them during pregnancy. A 10% incidence of serious maternal complications during pregnancy is widely quoted. We sought to review our recent cases and describe maternal and fetal outcomes in our patient population. Methods: Female patients aged 16–35 with aortopathy and a recent pregnancy (2008 ï¿½ 2015) were identified from the UHB database. Patients with a bicuspid aortic valve, structural congenital cardiac disease and coarctation of the aorta were excluded. Electronic and paper patient records and imaging results were reviewed to collect data regarding diagnosis, medical management, aortic dimensions, maternal obstetric and cardiovascular complications during or subsequent to pregnancy (within 1 year) and fetal outcome. Results: 23 patients were identified with the following diagnoses: Marfan syndrome (n = 14), Ehlers-Danlos (n = 4), Loeys-Dietz (n = 1) and undefined (n = 4) aortopathy. There were no patients with Turner syndrome within this cohort. One patient was excluded as she was under follow up for a family history of aortic disease which did not subsequently manifest itself in the patient. There were a total of 28 pregnancies. Beta blockers were prescribed in 21 pregnancies. Magnetic resonance imaging (MRI or MRA) was performed in 17 pregnancies. Maternal outcomes: Two patients had aortic dissections related to pregnancy. One was diagnosed immediately post partum in a woman with known Marfan syndrome and the other at 38 weeks gestation in a woman subsequently found to have to have Marfan syndrome. Both had successful emergency aortic root replacement, the second immediately after delivery of the fetus by caesarean section. One patient with undefined aortopathy presented acutely with chest pain and a rapidly dilating aorta; she had an emergency aortic root replacement at 22/40 gestation and was found to have a necrotising granulomatous aortitis. No patients died. Two patients had a change in aortic dimensions noted during pregnancy. Fetal outcomes: Two of the pregnancies resulted in therapeutic abortions related to occurrence of inherited lesions in the fetus. Conclusion: Although our numbers are small, the incidence of complications during pregnancy or immediately post partum are similar to those that we quote to our patients. Pregnant and post partum women complaining of severe chest pain should be brought to the immediate attention of senior staff and investigated urgently.